UKRAINE CRISIS AS A GLOBAL SECURITY CHALLENGE (Годишен зборник на Филозофски факултет - Скопје, 2022)
Russia’s invasion of Ukraine - Europe’s worst security crisis in decades - has prompted the EU to make unprecedented decisions on EU security, defence and enlargement. For the first time, decisions have been made to deliver deadly weapons to a third country and decisions to strengthen defence co-operation amid a new perception of the threat. The 2001 Temporary Protection Directive, which grants temporary residence to Ukrainian refugees, was activated for the first time. The overwhelming support for the UN resolution condemning the Russian invasion clearly proves that countries around the world see the invasion as an attack on global norms. However, policy makers in certain countries are managing the crisis in terms of their national interest. This paper will analyse the differences in regional and national attitudes regarding the events in Ukraine, ie geopolitical, economic and security factors that influence decision-making to deal with the Ukrainian crisis.